LATIONSHIP BETWEEN ANTENATAL EDUCATION AND MOTHERS' PSYCHOLOGICAL READINESS FOR CHILDLIFE AT THE BADESPUBLIC HEALTH CENTER, PASIRIAN DISTRICT - Rita Puspitaningsih; Agustina Widayati; Homsiatur Rohamtin (Lppm Unan, 2026)
Background: Childbirth is an anxiety-inducing experience for many pregnant women, making psychological preparedness a crucial factor in coping. Antenatal education is considered an effective intervention to improve mental preparedness, but empirical evidence on its effectiveness at the Bades Community Health Center, Pasirian District, is still limited. This study aims to analyze the relationship between the frequency of antenatal education and pregnant women's psychological preparedness for childbirth. Methods: The research design is a plan or plan created by the researcher as a framework for the activities to be implemented. This study employed a cross-sectional design. The study population included all pregnant women in their third trimester at the Bades Community Health Center in Pasirian District (N=32), using a total sampling technique. Results: The sperm rho statistical test indicated a p-value of 0.00 with a significance level (α) <0.05. Because the p-value is less than α, H2 is rejected and H1 is accepted. This indicates a relationship between antenatal education and maternal psychological preparedness for childbirth at the Bades Community Health Center in Pasirian District. Conclusion: The results of this study indicate a relationship between antenatal education and maternal psychological preparedness for childbirth at the Bades Community Health Center in Pasirian District.